Sex differences in shoulder acromiohumeral contact surface arc length on three-dimensional computed tomography imaging - Xi Chen; Tangzhao Liang; Chang Liu; Jianhua Ren; Shouwen Su; Xiangyu Long; Xiaopeng Yin; Yanbin Chen; Shihai Jiang; Kun Wang (Scientific Reports)
Abstract Anatomy-based guidelines for shoulder surgery have established the routine preoperative evaluation of the humeral head. Despite recognized sex differences in humeral head size, there has been limited investigation into sex-specific variations in acromiohumeral contact surface (AHCS) arc length. This study aims to assess sex differences in the AHCS arc length within a sample of the Chinese population. We retrospectively analyzed 169 normal shoulder CT images from a single medical center, collected between 2011 and 2021. The AHCS arc length was defined as the distance from the superior glenoid tubercle to the lateral edge of the greater tuberosity, measured using a three-dimensional reconstruction algorithm. Physiological reference values for the AHCS arc length were determined at three abduction angle intervals. Linear regression analysis was used to assess the correlation between the AHCS arc length and abduction angle in both sexes. The reference values for AHCS arc length were significantly lower in women across three abduction angle intervals (male 48.07 ± 3.37 mm vs. female 43.54 ± 2.54 mm, (0–10] °, p < 0.001; male 45.07 ± 2.34 mm vs. female 40.78 ± 2.06 mm, (10–20] °, p < 0.001; male 42.08 ± 2.03 mm vs. female 38.09 ± 2.44 mm, > 20 °, p = 0.001, respectively). Additionally, the AHCS arc length was linearly and negatively correlated with the abduction angle (male R2 = 0.436, p < 0.001; female R2 = 0.434, p < 0.001, respectively). The present study identified a significant sex difference in the anatomical AHCS arc length in a sample of the normal Chinese population. Preoperative assessment of the AHCS arc length may be necessary for certain shoulder surgeries in the future.